The Cyclic Oligoadenylate Signaling Pathway of Type III CRISPR-Cas Systems - Huang, Fengtao; Zhu, Bin (Frontiers in Microbiology, 2021)
Type III CRISPR-Cas systems, which are widespread in both bacteria and archaea, provide immunity against DNA viruses and plasmids in a transcription-dependent manner. Since an unprecedented cyclic oligoadenylate (cOA) signaling pathway was discovered in type III systems in 2017, the cOA signaling has been extensively studied in recent 3 years, which has expanded our understanding of type III systems immune defense and also its counteraction by viruses. In this review, we summarized recent advances in cOA synthesis, cOA-activated effector protein, cOA signaling-mediated immunoprotection and cOA signaling inhibition, and highlighted the crosstalk between cOA signaling and other cyclic oligonucleotide-mediated immunity discovered very recently.